2020
DOI: 10.1021/acs.inorgchem.0c01196
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Metathesis between AgNO3 and NaX (X = Cl, Br, I) and Ag2XNO3 Double-Salt Formation

Abstract: Here we describe real-time, in situ monitoring of mechanochemical solid-state metathesis between silver nitrate and the entire series of sodium halides, on the basis of tandem powder X-ray diffraction and Raman spectroscopy monitoring. The mechanistic monitoring reveals that reactions of AgNO 3 with NaX (X = Cl, Br, I) differ in reaction paths, with only the reaction with NaBr providing the NaNO 3 and AgX products directly. The reaction with NaI revealed the presence of a novel, short-lived intermediate phase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…Simple visual analysis of two-dimensional background-corrected diffractograms (Figure a) can reveal a plethora of information, such as the number of transformations occurring during milling and even preliminary identification of participating phases. If crystal structures of all participating phases are known, quantitative analysis of reaction profiles is accessible through a Rietveld refinement . Otherwise, qualitative reaction profiles can be extracted by a Pawley refinement or single-peak fitting .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple visual analysis of two-dimensional background-corrected diffractograms (Figure a) can reveal a plethora of information, such as the number of transformations occurring during milling and even preliminary identification of participating phases. If crystal structures of all participating phases are known, quantitative analysis of reaction profiles is accessible through a Rietveld refinement . Otherwise, qualitative reaction profiles can be extracted by a Pawley refinement or single-peak fitting .…”
Section: Methodsmentioning
confidence: 99%
“…If crystal structures of all participating phases are known, quantitative analysis of reaction profiles is accessible through a Rietveld refinement. 38 Otherwise, qualitative reaction profiles can be extracted by a Pawley refinement 39 or single-peak fitting. 1 The inclusion of an X-ray scattering standard, such as crystalline silicon, permits estimating homogeneity of the reaction mixture, quantification of the amorphous content, as well as determination of the instrument contribution to peak width and shape and therefore also to information such as average particle strain and size (Figure 3).…”
Section: Data Processingmentioning
confidence: 99%
“…More recently, Lukin and coworkers explored the ball-milling metathesis reaction between AgNO 3 and NaX (X = Cl, Br, I) to form AgX and NaNO 3 [ 113 ]. The reaction rates for milling reactions involving NaI and NaBr were similar and were significantly faster than those with NaCl, potentially due to the observed of the formation of the intermediate Ag 2 ClNO 3 , while the corresponding intermediates did not form with NaBr and NaI.…”
Section: Metathesis (Exchange) Reactionsmentioning
confidence: 99%
“…23,24 This was achieved through in situ monitoring of reaction mixtures using spectroscopic techniques (Raman, NMR and IR spectroscopies) and diffraction methods. 23–29…”
Section: Introductionmentioning
confidence: 99%
“…23,24 This was achieved through in situ monitoring of reaction mixtures using spectroscopic techniques (Raman, NMR and IR spectroscopies) and diffraction methods. [23][24][25][26][27][28][29] On the other hand, thermodynamic studies within the field of mechanochemistry have not yet received appropriate attention. Several reports focusing on solid-state thermodynamics clearly demonstrated that such an approach is fundamental for the systematic advancement of the field.…”
Section: Introductionmentioning
confidence: 99%